Role of DPP-4 and SGLT2 Inhibitors Connected to Alzheimer Disease in Type 2 Diabetes Mellitus - Sim, A Young; Barua, Sumit; Kim, Jong Youl; Lee, Yong-ho; Lee, Jong Eun (Frontiers in Neuroscience, 2021)
Alzheimer's disease (AD) is characterized by memory loss and cognitive decline. Additionally, abnormal extracellular amyloid plaque accumulation and nerve damage caused by intracellular neurofibrillary tangles and tau protein are characteristic of AD. Furthermore, AD is associated with oxidative stress, impaired mitochondrial structure and function, denormalization, and inflammatory responses. Recently, besides the amyloid β hypothesis, another hypothesis linking AD to systemic diseases has been put forth by multiple studies as a probable cause for AD. Particularly, type 2 diabetes mellitus (T2DM) and its features, including hyperinsulinemia and chronic hyperglycemia with an inflammatory response, have been shown to be closely related to AD through insulin resistance. The brain cannot synthesize or store glucose, but it does require glucose, and the use of glucose in the brain is higher than that in any other organ in the mammalian body. One of the therapeutic drugs for T2DM, dipeptidyl peptidase-4 (DPP-4) inhibitor, suppresses the degradation of incretins, glucagon-like peptides and glucose-dependent insulinotropic peptide. Sodium‐glucose cotransporter 2 (SGLT2) inhibitors, recently used in T2DM treatment, have a unique mechanism of action via inhibition of renal glucose reabsorption, which is different from the mechanisms of previously used medications. This paper reviews the pathophysiological relationship between the two diseases, AD and T2DM, and the pharmacological effects of therapeutic T2DM drugs, especially DPP-4 inhibitors and SGLT2 inhibitors.